The comparison of remimazolam and midazolam in bronchoscopic sedation: a systematic review and meta-analysis of randomized controlled trials - AbuJwaid, Yahya Kayed; Deeb, Salahaldeen; Amro, Alhareth M.; Asbeh, Yousef Abu (Frontiers in Medicine, 2025)
BackgroundEffective sedation is critical for bronchoscopy, ensuring patient comfort and procedural success. Midazolam, though widely used, has limitations such as longer induction and recovery times. Remimazolam, a novel ultra-short-acting benzodiazepine, offers rapid onset, faster recovery, and a safer profile, making it a potential alternative.Study design and methodsA systematic review and meta-analysis of four randomized controlled trials (RCTs) involving 630 patients compared remimazolam with midazolam for bronchoscopy sedation. Primary outcomes included induction time, recovery time, and rescue sedation rates. Secondary outcomes assessed procedural duration and adverse events. Random-effects models were used for analysis, and evidence quality was graded using GRADE criteria.ResultsRemimazolam reduced induction time by 3.2 min (95% CI: −5.51 to −0.91, p = 0.006) and recovery time (SMD: -0.976, 95% CI: −1.48 to −0.47, p < 0.001) compared to midazolam. Patients receiving remimazolam required less rescue sedation (OR: 0.223, 95% CI: 0.107 to 0.467, p < 0.001). No significant differences were observed in bronchoscopy duration or the incidence of intraoperative and postoperative complications, including hypoxia, hypotension, and nausea.ConclusionRemimazolam may reduce induction and recovery times and decrease the need for rescue sedation compared to midazolam. However, due to high heterogeneity and the limited number of studies, these findings should be interpreted with caution. Due to the limited number of studies and observed heterogeneity, further high-quality trials are necessary to confirm these findings.Clinical trial registrationClinicaltrial.gov, identifier: CRD42024623846.